Programa de prevención de riesgos laborales en el proceso de ensamble manual en la planta de ITEK - Martinez-Zúñiga, Gerson-José (Instituto Tecnológico de Costa Rica, 2018)
The present project was carried out in the company ITEK Soluciones Integrales S.A., in the manual assembly plant of the catheter dispensers. Workers at the plant are exposed to specific conditions of a clean room, this means that some variable must remain in a standardized manner. The goal is to propose a prevention program to the main occupational hazards present during the process at the ITEK building. For the analysis of the current situation, samples were taken, checklists in safety and psychosocial, and ergonomic analysis by the same manual handling and the type of work handled, analyzing both hand methods and whole body. The dangers were evaluated through the INTE 31-06-07:2011 - Guide for the identification of hazards and the evaluation of risks. Using this also for the creation of an emergency response plan standardized by the CNE. It was determined that there are risks mainly due to repetitive work and thermal comfort in the clean room, and safety issues in the storage, signaling and fire areas. This is generated by the lack of work procedures, training in safety and hygiene and little risk prevention, which can generate unsafe acts during the work, increasing the possibility of suffering short and long-term injuries. It is proposed the preparation of a risk prevention program proposal for manual assembly activities, in order to generate safe work conditions and practices with work instructions, as well as providing general tools in various areas for the use of the company. in other projects. In addition to the plan containing the necessary procedures and tools for emergency response.
Proyecto de graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2018.
Keywords: Riesgos; Prevención; Seguridad; Ergonomía; Condiciones; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas::Occupational medicine